PENGARUH DEBT EQUITY RATIO, CURRENT RATIO, MATURITY DAN SIZE TERHADAP BOND RATING (STUDI PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BEI PERIODE 2012-2017) - Ekka Pratama; Revan Andhitiyara (Sekolah Tinggi Ilmu Ekonomi Jayakarta, 2020)
This research is aims to analyze the influence of Debt Equity Ratio, Current Ratio, Maturity and Size on Banking Company Bond Ratings on the Indonesia Stock Exchange for the period 2012-2017. The study uses secondary data from the annual financial statements of selected companies downloaded from the official website of the Indonesia Stock Exchange. The sampling technique uses purposive sampling method. The sample in this study consisted of 11 banking companies. Data analysis was performed by testing hypotheses both partially and simultaneously. The analytical method used is binary logistic regression with a significance level of 5% and 10%. Based on the results of the study showed that partially Debt Equity Ratio (DER) variables did not significantly influence Bond Rating, Current Ratio (CR) had a positive and significant effect on Bond Rating, Maturity had no significant effect and Size had a negative and not significant effect on Bond Rating. Simultaneously, a significance value of 0.002 is obtained, because the significance value is smaller than 0.05, then all variables affect the Bond Rating. Based on the results of the study, it is expected to be able to be an evaluation material for banks related to Bond Rating and its relationship with DER, CR, Maturity, and Size so that the bank can do the processing properly.